MENGUKUR EFEKTIVITAS TAGLINE IKLAN TELEVISI MINUMAN RINGAN TEH BOTOL SOSRO DENGAN METODE CUSTOMER RESPONSE INDEX (CRI) (Studi pada Mahasiswa Program Studi Manajemen Universitas Nusantara PGRI Kediri Angkatan 2014) - Muhammad Dian Ruhamak; Evi Husniati Syai'dah (Universitas Kadiri, 2017)
Abstract Tagline is one way to make the customer always remember the product with the catchprase. Teh Botol Sosro is one of the products whose ads have a catchy tagline or catch phrase. In 2000 Teh Botol Sosro replaced his tagline with